PENDIDIKAN ISLAM DALAM SISTEM PENDIDIKAN NASIONAL - Moh Sakir (IAIN Ponorogo, 2014)
Abstract: Existence of Islamic education have big role in the education history at Indonesia, but the role still haven’t full independence it’s political and also its implementation. This matter look by law that formal Islamic education which known by government is Islamic education. Known education is madrasah which have been registered through MAPENDA under Kemenag. Islamic Boarding School still in confession of Moslem society alone which only accepted by Moslem society itself. Therefore Islam people fight not only conducting education but also overall of financing side, education political and independence. Thereby Islamic education require to be improved again by entire all stakeholder Moslem society for the sake of Islamic education as same as Islam aspiration. Appearance of public education system and Islamic education are two sides cannot separate each other in national education system, both related and equipping each other. In the one side the aim of national education is to develop student’s potency in order to become god-fearing and religious, good manner, healthy, knowable and expected to be democratic citizen and responsible.ملخص: أسهم التربية الإسلامية اسهاما كبيرا في تاريخ التربية الإسلامية في إندونيسيا. لكنّ وجودها لم يُعط لها الاستقلالية التامة سياسيا وتطبيقيا. وهذا يظهر قانونيا رسميا أن التربية الإسلامية المعترفة لدى الحكومة هي التربية المتميزة بالتعاليم الإسلامية، وهي المدارس الإسلامية المسجلة في مجلس التربية الأساسية في وزارة الشؤون الدينية. أما البسنترينات فهي معترفة لدى المجتمع المسلم أنفسهم. لذا فإن جهاد المسلمين في التربية لا يكون فقط في تطبيق التربية فحسب لكنه في جميع الجوانب، التكاليف والسياسة التربوية والاستقلالية. بهذا لابد من ترقية التربية الإسلامية الموجودة بمشاركة جميع الشخصيات في المجتمع المسلم لتكون التربية الإسلامية موافقة بما يريده الإسلام. فظهور النظام التربوي العام والنظام التربوي الإسلامي في النظام التربوي الإندونيسي لا يمكن فصلهما، لأنهما مرتبطان ولكل خصائصه ومميزاته المتكاملتان. في جانب أن أهداف التربية الوطنية هي تنمية قدرات التلاميذ ليكونوا أناسا مؤمنين بالله ومتقين، ومتخلقين بأخلاق كريمة، أصحّاء جسميا ولهم علوم ويرجى أن يكونوا مواطنين أمناء وديمقراطيين. Keywords: Pendidikan Islam, pesantren, madrasah.